The Role of Islamic Religious Education Teachers as Exemplary Models (Usawatun Hasanah) in the Era of Disruption: A Literature Study from the Perspective of Psychology and Islamic Education - Indramawan, Anik; Tohawi, Agus; Anwar, Muhamad Ali Anwar; Mastur, Mastur; Fuad, Nur; Utomo, Achmad Fauza Setyo; Rahma, Leily Vidya (Westscience Press, 2024)
The era of disruption, which is marked by rapid technological developments, changes in social values, and global information flows, creates complex challenges for the formation of students' character. In this context, Islamic Religious Education (PAI) teachers are required not only as teachers, but also as living exemplary models (uswatun hasanah). Integration of the perspectives of Psychology and Islamic Education is needed to analyze this strategic role comprehensively. This research aims to analyze the role, challenges and strategies of Islamic Education Teachers as exemplary models in an era of disruption through a literature synthesis from the perspective of Psychology and Islamic Education. Research findings show that: (1) The concept of uswatun hasanah in Islamic Education is in line with social learning theory in Psychology, where individuals learn through observation and imitation; (2) The PAI teacher's role includes being a role model in morals, wise use of technology (digital ethics), and mental resilience; (3) The main challenges include moral degradation, competition with the influence of digital media, and teacher workload; (4) Effective strategies include strengthening digital-pedagogical competence, building positive personal branding on social media, and collaborating with parents. The role of PAI teachers as uswatun hasanah in the era of disruption is becoming increasingly critical and complex. An integrative approach between Islamic values ​​​​and psychological principles can strengthen teacher effectiveness in shaping the character of students. Increasing teacher competency and systemic support from educational institutions is very necessary.